Prevalence of intestinal parasites during pre- and post-COVID-19 pandemic at a tertiary care center in Lebanon - Hani El Achkar; Lina Ghandour; Sarah Farran; George F Araj (Journal of Infection in Developing Countries)
Introduction: Intestinal parasitic infections (IPIs) are a major medical and public health problem, especially in developing countries. This study aimed at comparing the prevalence and types of IPI during pre- and post-COVID-19 pandemics, and with data reported in Lebanon a decade ago.